Alleviatory effects of Danshen, Salvianolic acid A and Salvianolic acid B on PC12 neuronal cells and Drosophila melanogaster model of Alzheimer's disease. (28th October 2021) - Tan, Florence Hui Ping; Ting, Andrew Chung Jie; Leow, Ban Guan; Najimudin, Nazalan; Watanabe, Nobumoto; Azzam, Ghows
Abstract: Ethnopharmacological relevance: Danshen water extract (DWE), obtained from the Salvia miltiorrhiza Bunge (Family Lamiaceae) root, is usually employed in Chinese traditional medicine as treatment to cardiovascular ailments and cerebrovascular diseases. Intriguingly, the extract was also found to contain vast beneficial properties in Alzheimer's disease (AD) treatment. Aim of the study: Alzheimer's disease is the most significant type of neurodegenerative disorder plaguing societies globally. Its pathogenesis encompasses the hallmark aggregation of amyloid-beta (Aβ). Of all the Aβ oligomers formed in the brain, Aβ42 is the most toxic and aggressive. Despite this, the mechanism behind this disease remains elusive. In this study, DWE, and its major components, Salvianolic acid A (SalA) and Salvianolic acid B (SalB) were tested for their abilities to attenuate Aβ42's toxic effects. Methods: The composition of DWE was determined via Ultra-Performance Liquid Chromatography (UPLC). DWE, SalA and SalB were first verified for their capability to diminish Aβ42 fibrillation using an in vitro activity assay. Since Aβ42 aggregation results in neuronal degeneration, the potential Aβ42 inhibitors were next evaluated on Aβ42-exposed PC12 neuronal cells. The Drosophila melanogaster AD model was then employed to determine the effects of DWE, SalA and SalB. Results: DWE, SalA and SalB were shown to be able to reduce fibrillation of Aβ42. When tested on PC12 neuronal cells, DWE, SalA and SalB ameliorated cells from cell death associated with Aβ42 exposure. Next, DWE and its components were tested on the Drosophila melanogaster AD model and their rescue effects were further characterized. The UPLC analysis showed that SalA and SalB were present in the brains and bodies of Drosophila after DWE feeding . When human Aβ42 was expressed, the AD Drosophila exhibited degenerated eye structures known as the rough eye phenotype (REP), reduced lifespan and deteriorated locomotor ability. Administration of DWE, SalA and SalB partially reverted the REP, increased the age of AD Drosophila and improved most of the mobility of AD Drosophila . Conclusion: Collectively, DWE and its components may have therapeutic potential for AD patients and possibly other forms of brain diseases. Graphical abstract: Image 1 Highlights: DWE, SalA and SalB reduced fibrillation of Aβ42 in vitro . DWE, SalA and SalB ameliorated PC12 cells from cell death associated with Aβ42 exposure. Feeding of DWE, SalA and SalB partially reverted the REP, increased the age and improved the mobility of AD Drosophila .